VARIATIONS IN PATTERNS OF BRANCHING OF THE THYROCERVICAL TRUNK. - HUMBERTO FERREIRA ARQUEZ (International Journal of Pharma and Bio Sciences, 2015)
The thyrocervical trunk or thyrobi cervicoscapular trunk of faraboeuf is a branch most commonly arises from the upper portion of the first segment of the subclavian artery. Trunk branches can show many variant. In view of this significance a total of 13 human bodies (26 sides) were used for this study. The lateral region of the neck was dissected carefully and photographed in the Morphology Laboratory at the University of Pamplona. Unilateral anatomical variations was found in a 75-year-old male cadaver with presence of the double suprascapular artery; the first suprascapular artery and dorsal scapular artery has its origin by a common stem arising from the thyrocervical trunk, the second suprascapular artery has its origin directly from subclavian artery. Other branches exhibited high variations. Variability of the thyrocervical trunk and its branches must be considered of interest given the frequency with this region is involved in both diagnostic and therapeutic procedures.